Redes organizacionais como estratégia para inserção dos negócios na cadeia produtiva do leite: o caso da Associação de Produtores Rurais de Pires - Sanabio, Marcos Tanure (2008)
This thesis discusses the formation of organizational networks of small rural producers as a strategy for their insertion in the dairy production chain and for expanding their businesses to face the globalization process. The multiple facets - economical, political, social and cultural - of these networks will be analyzed, which predict deep changes in the relation among organizations, mainly for the search of high levels of competitiveness and ability to prosper. Competitive dynamics requires changes in organizations that go beyond internal boundaries and are sustained by the formation of organizational networks involving various actors and agents. Small businesses - which generally are at a competitive disadvantage with big organizations and are the weaker link in the productive chain - will be highlighted. The structure of organizational networks has constituted an alternative for the protection of small businesses. This study is a qualitative research and a case study of Rural Producers Association of Pires (APRP), with head office in Monte Verde district, in the city Juiz de Fora, state of Minas Gerais, Brazil. A successful experience of small rural producers was investigated in detail, aiming at answering the question: do organizational networks - the small producers associations - in the dairy sector bring benefits to their affiliate and grant favorable conditions for improving their competitiveness in the dairy production chain? From an analysis and interpretation model structured on three components - technical-economic, organizational relations and social capital - it is demonstrated that profits and benefits are significant. Furthermore, the organizational relations between actors and agents are supported by high levels of cooperation and trust, in democratic and participative administration, with the use of governance mechanisms and with great benefits of infra-structure and public and social equipment for the community.